PENERAPAN PEMBELAJARAN BERBASIS PROJEK UNTUK MENINGKATKAN KETERAMPILAN BERKOLABORASI SISWA DALAM PEMBELAJARAN ILMU PENGETAHUAN SOSIAL - Al Aziizah, Hafshoh; Estiningrum, Farida; Mardiani Zain, Ita; Jabir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to improve the collaboration skills of second-grade students at SMP Negeri 28 Surabaya by applying the Project Based Learning (PjBL) Model. The type of this research is a collaborative classroom action research (PTKK). This study uses a spiral spin model design, developed by Kemmis and Mc Taggart, was conducted in 2 cycles. Each cycle consists of 4 stages, namely the planning stage, implementation, observation, and also reflection. The subject of this research were 34 second-grade students. Data collection techniques are in the form of observation, interviews and documentation. Data analysis used is descriptivequalitative and quantitative. The results showed that the Project-Based Learning Model (PJBL) can improve collaboration skills in each cycle that has been indicated by the percentage of completeness in the pre-action obtained an average value of 73%, in the cycle I it increased to 81% and in cycle II increased sharply to 92%.